The Effectiveness of Family Communication Strategies for Family Members with Health Problems: A Systematic Review - Siti Riskika; Melinda Restu Pertiwi; Nessy Anggun Primasari; Niswa Salamung (Universitas Bondowoso, 2020)
Introduction: Many things are done by a person to get peace in his life, but sometimes someone does not realize the importance of interacting with other people, in this case communication. Communication is very crucial in life, especially in family life. Someone who is experiencing illness also needs clear communication to help the healing process, be it communication with family or communication with health workers. Method: The literature search was carried out by looking for literature studies in Scopus and in ScienceDirect with the theme of communication in the family. Result: After applying the eligibility criteria in the review, the 15 studies that had been obtained were included. The 15 studies, it shows that the communication provided by the family to other family members is very important in supporting the recovery of a sick family member, even a baby who is sick will gradually improve if he gets good communication from his mother, in the form of communication with physical contact. and attachment. The study of communication is important considering that many do not understand that communication is very important in life. Effective and open communication is also one of the keys to achieving a harmonious life in the family. Conclusion: Effective and open communication is important to apply, especially in family life, and also in the hospital environment, good communication between health workers, patients and families will help heal patients who are experiencing illness.